Lectin–epithelial interactions in the human colon. (19th November 2008) - Rhodes, Jonathan M.; Campbell, Barry J.; Yu, Lu-Gang
Abstract : Similar changes in glycosylation occur in the colonic epithelium in inflammatory conditions such as ulcerative colitis and Crohn's disease and also in colon cancer and precancerous adenomatous polyps. They include reduced length of O-glycans, reduced sulfation, increased sialylation and increased expression of oncofetal carbohydrate antigens, such as sialyl-Tn (sialylα2-6GalNAc), and the TF antigen (Thomsen–Friedenreich antigen) Galβ1-3GalNAcα-Ser/Thr. The changes affect cell surface as well as secreted glycoproteins and mediate altered interactions between the epithelium and lectins of dietary, microbial or human origin. Different TF-binding lectins cause diverse effects on epithelial cells, reflecting subtle differences in binding specificities e.g. for sialylated TF; some of these interactions, such as with the TF-binding peanut lectin that resists digestion, may be biologically significant. Increased TF expression by cancer cells also allows interaction with the human galactose-binding lectin, galectin-3. This lectin has increased concentration in the sera of patients with metastatic cancer and binds TF on cancer cell surface MUC1 (mucin 1), causing clustering of MUC1 and revealing underlying adhesion molecules which promote adhesion to endothelium. This is likely to be an important mechanism in cancer metastasis and represents a valid therapeutic target. Tools are now available to allow fast and accurate elucidation of glycosylation changes in epithelial disease, characterization of their potential lectin ligands, whether dietary, microbial or human, and determination of the functional significance of their interactions. This should prove a very fruitful area for future research with relevance to infectious, inflammatory and cancerous diseases of the epithelia.